Reconciling alignment, efficiency, and agility in IT project portfolio management: Recommendations based on a revelatory case study. Issue 2 (February 2020) - Hoffmann, David; Ahlemann, Frederik; Reining, Stefan
Abstract: Current developments put significant pressure on IT project portfolio management (IT PPM), increasingly requiring IT project portfolios to be strategically aligned and efficient yet agile. Accordingly, our aim is to identify IT-PPM-related tensions among the three design goals alignment, efficiency, and agility, and to elaborate a set of design principles that will provide organizations with recommendations for reconciling these goals. We conduct our research trough the theoretical lens of Activity Theory. Our findings are based on a revelatory case study in the financial services sector and are evaluated through focus group discussions and expert interviews. Highlights: Tensions that hamper IT project portfolio management's (IT PPM) effectiveness are studied. IT PPM is conceptualized from an Activity Theory perspective and applied to the investigation of a revelatory case. Complex dynamic power structures and opportunistic behavior of stakeholders create vicious circles of ineffective IT PPM. We iteratively develop and evaluate principles for an aligned and agile yet efficient IT PPM.